2019
DOI: 10.12998/wjcc.v7.i18.2712
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of 14v-lymph node dissection to D2 dissection for lower-third gastric cancer

Abstract: BACKGROUNDRadical gastrectomy with D2 lymph node (LN) dissection is the standard surgical procedure for patients with resectable gastric cancer (GC). In the fifteenth edition of the Japanese Classification of Gastric Carcinoma, the 14v LN (LNs along the root of the superior mesenteric vein) was defined as the regional gastric LN. The efficacy of 14v LN dissection during radical distal gastrectomy for lower-third GC remains controversial.AIMTo analyze whether the addition of 14v LN dissection improved the survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…First, this is a retrospective study with inherent selection bias, the clinical characteristics are quite different in the 2 comparison groups. 16 So we have used the PSM analysis to lessen the baseline differences from nonrandom assignments. Second, given the heterogeneity of GNEC, its prognosis is also significantly impacted by the clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…First, this is a retrospective study with inherent selection bias, the clinical characteristics are quite different in the 2 comparison groups. 16 So we have used the PSM analysis to lessen the baseline differences from nonrandom assignments. Second, given the heterogeneity of GNEC, its prognosis is also significantly impacted by the clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies (10,22,23,27,28) have confirmed that adding 14v to D2 dissection improves survival outcomes for patients with distal advanced GC (Table II). Eom et al (22) confirmed that 14v dissection improves the OS rates of patients with clinical stage III/IV GC in the middle or lower third of the stomach.…”
Section: No 14v Ln Dissection For Distal Local Advanced Gcmentioning
confidence: 95%
“…From the viewpoint of the distance from the tumor to the main lymphatic flow, presumably, GC located on the greater curvature wall is more likely to metastasize to lymph node station No.6 (16), which has lymphatic flow to stations No.14v and No.16, making lymphadenectomy difficult (17)(18)(19). Jung et al reported a worse prognosis in patients with GC on the greater curvature than those in patients with GC with other locations (15).…”
Section: Comparisons Of 5-year Overall Survival (Os) Rates According ...mentioning
confidence: 99%